The effect of drug dosage calculation training program on math anxiety and nursing students' skills: A non-randomized trial study - Leila Sayadi; Alireza Nikbakht Nasrabadi; Amin Hosseini (Tehran University of Medical Sciences, 2021)
Background & Aim: Drug dosage calculation is one of the main skills in the drug administration process that requires sufficient knowledge about mathematical calculations and drug dosage; in addition, lack of math anxiety is required for drug dosage calculation as well. The aim of this study was to determine the effect of mathematical calculation and drug dosage training programs on math anxiety and nursing students' drug dosage calculation skills. Methods & Materials: The present research was a non-randomized trial study. As a result of available sampling, 80 nursing students (40 in the control group and 40 in the intervention group) participated in the study. The study intervention included a mathematical and drug dosage training program including lecture, workshop, and practicing mathematical and drug calculations at the patient's bedside. The data were collected using a demographic, Betz' math anxiety, and drug dosage calculation skills questionnaires. Finally, descriptive and analytical statistics were used to analyze the data. Results: The two groups were homogeneous in terms of demographic variables, math anxiety, and drug calculation scores in the baseline. Two-way ANOVA with repeated measures indicated the significant effect of the group on math anxiety (P = 0.024). Given the interaction between group effect and time for the drug dosage calculations, the comparison of the differences between the second time and third time scores of the baseline scores ​​showed a statistically significant difference between the two groups in terms of drug dosage calculations (P <0.001). Conclusion: Implementation of a drug dosage calculation training program for nursing students can lead to the reduction of math anxiety and improvement of the drug dosage calculations; this can ultimately help improve patient safety.